Representation of Parent and Adolescent Conflicts in Film Copying Light - Verdynand Anhar Kurniawan; Rahmawati Zulfiningrum (CV. Rayyan Dwi Bharata, 2023)
Film has become a means of necessity for society. Films can present a form of real life reality experienced by everyday people. The purpose of this study is to find out how the conflict between parents and children is represented in the film Copying Light. The method used in this research is qualitative by using Roland Barthes's semiotic analysis method. This method is used because this research is included in the research category with research subjects that are described using existing facts. The final result of this study based on the discussion above is that this study uses the Roland Barthes Semiotics method, which consists of Denotation, Connotation, and Myth. Meanwhile, the theory used in this research is Parent and Child Conflict Theory which consists of Family Conflict based on Social Agreement, Family Conflict based on Responsibility, Family Conflict based on Family Relations, Family Conflict based on Social Life, Family Conflict based on School.